Latest insights in therapeutic options for systemic right ventricular failure: a comparison with left ventricular failure. Issue 12 (25th November 2008) - Winter, M M; Bouma, B J; Groenink, M; Konings, T C; Tijssen, J G P; van Veldhuisen, D J; Mulder, B J M
Abstract : The number of adult patients with a systemic right ventricle (RV) is steadily increasing. Survival is relatively good in these patients, but deterioration of the systemic RV seems inevitable. Although therapeutic options for patients with LV failure are well established, their role in patients with systemic RV failure is often undefined. To appreciate the potency of LV failure therapy in patients with a systemic RV, insight into pathophysiology of systemic RV failure and into recent developments in therapeutic research are indispensible. This review provides these insights, and will facilitate and ameliorate therapeutic decision making in patients with a systemic RV.